Allocation and metabolism of naturally occurring dietary amino acids in the Oriental hornet. (December 2021) - Bodner, Levona; Bouchebti, Sofia; Levin, Eran
Abstract: Oriental hornet ( Vespa orientalis ) foragers are strong, long-distance flyers exhibiting a high metabolic rate. Accordingly, they feed on carbohydrate-rich diets, such as floral nectar and larval secretions. These nutritional sources, in addition to carbohydrates, also contain free amino acids (AAs). Leucine, glycine, and proline are three common AAs in the diet of social wasps. Using diets enriched with carbon-specific ( 13 C1 ) isotopically labeled leucine, glycine, and proline, and a cavity ring-down spectroscope (CRDS) stable carbon isotope analyzer, we examined the metabolism of these AAs, their allocation in the hornets' respiration during rest and activity, and their incorporation into the body tissues. In hornets that consumed 13 C proline, we detected the heavy isotope only in the exhaled CO2, suggesting that proline was utilized solely as a metabolic fuel and was not incorporated into their body (i.e., as protein). Labeled carbons from glycine and leucine, in contrast, were found in all the examined tissues (i.e., muscles, brain, fat bodies, ovaries, and venom glands), and were also utilized as a metabolic fuel, but mostly during rest. Using AAs labeled with a specific stable carbon isotope, we demonstrate the compatibility between the hornet's metabolic requirements and AA use, in both the living organism as a whole and in its different body tissues. Graphical abstract: Image 1 Highlights: Adult hornets feed mainly on floral nectar and hornet larval secretions, which contain mainly carbohydrates and free amino acids. Hornets were fed with artificial nectar containing 13 C1 isotopically labeled amino acids, common in their diet: glycine, leucine, and proline. At rest, hornets utilized all three amino acids as metabolic fuel. During the active phase, hornets utilized mostly proline as metabolic fuel. While dietary glycine and leucine were detected in body tissues, dietary proline was utilized only as metabolic fuel.